Retail Design and shopping experience in phygital spaces – Theory and practice - Sanzi, Gianpietro; Cattani, Airton; Scherer, Fabiano (DAT Journal, 2023)
The purpose of this psaper is to bring to discussion some subsidies for retail design decisions, considering the reflections regarding some shopping experience at phygital stores. In other words, brick-and-mortar stores that include digital technologies. The study starts from a bibliographic review about retail design and shopping experience at these stores. The output of this work has been analyzed and compared to retailers statements and professional retail designers, during the 2022 Latin American event for the retail sector, last September (2022). The testimonies confirm the integration necessity of the emerging technologies with the traditional stores in order to improve the consumer experience and reflect empirically the theoretical recommendations related to retail design.